720 Outcomes of Conservative Management of Acute Appendicitis During The COVID-19 Pandemic. (4th May 2021) - Oxenham, M; Jull, P; Karunaratne, D; Laskar, N; Harshen, R
Abstract: Introduction: During the SARS-CoV-2 (COVID-19) pandemic, appendicitis was managed conservatively to reduce peri-operative mortality; spread of infection; and hospital admissions. We describe the outcomes observed from conservative management during the pandemic. Method: This prospective single centre study included all patients with clinically acute appendicitis between 31/3/2020 to 31/5/2020. Length of admission and 30-day complications were recorded. This was compared to retrospective data from 31/3/2019 to 31/4/2019. Results: Of the 35 patients included between 31/3/2020 to 31/5/2020: 19 patients were managed conservatively with antibiotics; 8 required operative management after trial of antibiotics; and 8 required surgery on admission. Of the initially conservatively managed patients, three suffered complications (Clavien Dindo >1). Length of admission in conservative patients averaged 1.3 days (0-5 day range). In May 2019, 30 patients admitted with clinical appendicitis were all managed with appendicectomy. The average admission was 2.93 days (1-50 day range) with 4 patient complications. There was no difference (P = 0.22) when comparing the length of admissions within the pandemic and non-pandemic cohorts. Conclusions: Our study demonstrates no increase in complications or length of admission during the pandemic. We support the recommendation that conservative management of uncomplicated appendicitis is continued during the COVID-19 pandemic.